Proyecto de inversión para prevenir el síndrome de muerte infantil súbita (smis), mediante la importación y comercialización de un detector de respiración - Parreño Moran, Carissa (2009)
The purpose of this project is to make you know a product that is going to help children to avoid the SMIS, that in short words is the unexplained dead in a children that have less that one year